Gerges, Fawaz A. The Rise and Fall of Al-Qaeda. New York, Oxford University Press, agosto 2011, 272. ISBN 978-0-19-979065-4 - Espinosa Marty, Consuelo (Estudios Avanzados, 2012)
Gerges, Fawaz A. The Rise and Fall of Al-Qaeda. New York, Oxford University Press, agosto 2011, 272. ISBN 978-0-19-979065-4